Maritime claims and underwater archaeology - Aznar Gómez, Mariano J., 1965- (Leiden ; Boston)
131 sayfa
Keywords: “To what extent can underwater archaeology and underwater cultural heritage support a State’s maritime claim? Many States have plausibly extended their maritime legislative and executive jurisdiction to the outer limit of the contiguous zone to better protect underwater cultural heritage. However, some States - such as Canada in the Arctic, China in the South China Sea, or Russia in Crimea - are going further, claiming sovereignty over disputed maritime areas or even the high seas. Maritime Claims and Underwater Archaeology, aimed at internationalists and archaeologists, critically assesses these recent practices, reviewing this search for buried sovereignty from a legal, historical, and ethical perspective.” --